Penggunaan Papain dari Buah Pepaya Sebagai Peningkat Kualitas pH Nata De Coco yang Difermentasi oleh Acetobacter xylinum - Zulfiana Zulfiana; Samingan Samingan; Zairin Thomy (Biotik, 2018)
A study was carried out on the use of papain from papaya as quality enhancer for nata de coco which is fermented by Acetobacter xylinum in industrial home business in Cot Geundreut Village, Blang Bintang Aceh Besar.  The aim of the study was to find out whether the use of Papain can improve the quality of color, texture, pH and taste of nata de coco. The study used a complete factorial randomized design, with the concentration of papaya and papaya sap was 5 mL/L, 10 mL/L, 20 m/L, 30 mL/L, 50 mL/L. In ANAVA, the treatment showed a significant effect of papaya juice and papaya sap on nata de coco quality (Papaya juice (26,989) > Ftable (2,61); α = 0,05 and Papaya sap (122,542) > Ftable (2,61); α = 0,05. The treatment has no significant effect to the color, but it increased the pH of nata de coco to 6-7, and the structure of nata de coco became less chewy. However, although the organoleptic test does not affect the taste of nata de coco, respondents still prefer nata de coco without treatment because it has no trace of papaya and papaya sap smell. Therefore, this study needs further research to get more information about the taste.